Stratified Sampling Applied to Estimation of the Volumetric Fraction of Alumina in Cast Metal Matrix Composites - Ranieri, K.; Costa, A. F. B.; Kiyan, C. (Carl Hanser Verlag, 2009)
In this paper, we propose a statistic procedure for estimating the amount of alumina incorporated in a particulated metal matrix composite synthesized by the stir casting method. Composite specimens, consisting of A356 Al alloy matrix material containing 5 wt% of alumina particles, were prepared using the compocasting technique. An intermediate traversal section of each composite ingot was stratified into 24 parts and the volumetric fraction of alumina was measured by image analysis at 279 separate points to study the alumina distribution in the material. Alumina particle distribution was observed to have considerable heterogeneity. The stratification technique employed in this study permits an ideal trade-off between the accuracy of the estimated alumina and the required measurement labor.